Recent Advances in Multiresponsive Flexible Sensors towards E‐skin: A Delicate Design for Versatile Sensing - Li, Wu‐Di; Ke, Kai; Jia, Jin; Pu, Jun‐Hong; Zhao, Xing; Bao, Rui‐Ying; Liu, Zheng‐Ying; Bai, Lu; Zhang, Kai; Yang, Ming‐Bo; Yang, Wei (Small (Weinheim an der Bergstrasse, Germany), 2022)
Multiresponsive flexile sensors with strain, temperature, humidity, and other sensing abilities serving as real electronic skin (e‐skin) have manifested great application potential in flexible electronics, artificial intelligence (AI), and Internet of Things (IoT). Although numerous flexible sensors with sole sensing function have already been reported since the concept of e‐skin, that mimics the sensing features of human skin, was proposed about a decade ago, the ones with more sensing capacities as new emergences are urgently demanded. However, highly integrated and highly sensitive flexible sensors with multiresponsive functions are becoming a big thrust for the detection of human body motions, physiological signals (e.g., skin temperature, blood pressure, electrocardiograms (ECG), electromyograms (EMG), sweat, etc.) and environmental stimuli (e.g., light, magnetic field, volatile organic compounds (VOCs)), which are vital to real‐time and all‐round human health monitoring and management. Herein, this review summarizes the design, manufacturing, and application of multiresponsive flexible sensors and presents the future challenges of fabricating these sensors for the next‐generation e‐skin and wearable electronics. Multiresponsive flexible sensors susceptible to various stimuli including strain, temperature, humidity, etc., have been rapidly emerging due to their great potential application in e‐skins. Thus, the recent progress of multiresponsive flexible sensors including the design strategies (the choices of sensing materials and mechanisms, and structure designs and fabrication methods), applications and prospects is reviewed to promote further development of e‐skins.